Association Between Family Functioning and Health-related Quality of Life in Stroke Survivor-Informal Family Caregiver Dyads - Chia-Chi Li; Su-Ju Tsai; Jo-Ching Tai; Tzu-Jung Wu; Shu-Mei Tsai; Shu-Chuan Kao; Hsiang-Chu Pai (Elsevier, 2024)
summary: Purpose: Stroke survivors and their informal family caregivers may share the impact of the disease, which may affect family functioning and quality of life (QoL) for both. This study compared the perceptions of stroke survivors and informal family caregivers regarding family functioning and QoL and examined the QoL of those reporting effective versus ineffective family functioning. Methods: A cross-sectional study design and convenience sampling were used. Stroke survivor-informal family caregiver dyads were recruited from a medical university hospital. We assessed participants' demographic and clinical variables, including disease severity, family functioning, and QoL. Independent t-test, paired t-test, Wilcoxon signed-rank test, and Mann-Whitney U test were used to analyze the data. Results: Seventy-one stroke survivor-informal family caregiver dyads participated in the current study. Most stroke survivors and informal family caregivers reported effective family functioning, with no significant differences. However, significant differences existed in the seven domains (physical functioning, role-physical, bodily pain, general health, vitality, social functioning, and role-emotional) of QoL, except emotional health. Stroke survivors reporting ineffective family functioning had a significantly lower mental component summary score, unlike informal family caregivers. Conclusions: Our findings suggest that family functioning is crucial to ensure stroke survivors' QoL, particularly regarding their mental health. Health professionals should prioritize mental health assessments and provide appropriate care interventions for stroke survivors in the first 1-6 months after stroke onset.